Strengthening the labour force participation of low-qualified individuals in Europe - Jan Paul Heisig; Carla Hornberg; Heike Solga (European View, 2024)
This article addresses the labour market challenges faced by adults with low formal qualifications. While low-level formal qualifications are usually associated with a lower skill level, it is crucial to recognise the large heterogeneity of skills within the group of low-qualified individuals in all countries. Although better skills enhance the job opportunities of low-qualified workers, their lack of formal qualifications limits their job prospects, even if they are as skilled as more highly qualified workers. Their placement in low-skilled jobs has implications for their participation in further training. Limited access to adult training is primarily caused by employment in these low-skilled jobs rather than by differences in cognitive skills or motivation to learn. Policies should, therefore, focus on strategies that improve training opportunities in the workplace, and employers should consider modifying hiring methods to place greater weight on actual skills in addition to formal qualifications. Both approaches would, economically speaking, enable the utilisation of the existing skill potential of low-qualified adults and, socially, enhance the employment prospects of this group.
Keywords: 330